Ameliorating Interfacial Issues of LiNi0.5Co0.2Mn0.3O2/Poly(propylene carbonate) by Introducing Graphene Interlayer for All‐Solid‐State Lithium Batteries. Issue 7 (17th February 2020) - Zhuang, Zilong; Yang, Lezhi; Ju, Bowei; Lei, Gang; Zhou, Qian; Liao, Hanxiao; Yin, Ao; Deng, Zhiyuan; Tang, Yating; Qin, Shibiao; Tu, Feiyue
Abstract: Interfacial side reaction mechanism between poly(propylene carbonate) solid polymer electrolyte (PPC‐SPE) and LiNi0.5 Co0.2 Mn0.3 O2 cathode (c‐NCM) is investigated. Ni 3+ and Co 4+ species generated by electrochemical oxidization process can decompose poly(propylene carbonate) to aldehyde. To address this interface issue, a graphene interlayer is introduced to the LiNi0.5 Co0.2 Mn0.3 O2 cathode surface via a facile method to improve cycle stability, rate capability and interfacial resistance. After 50 cycles at 0.3 C, the capacity retention of G@c‐NCM is 97.9 % and the resistance is less than 20 Ω, the improved electrochemical properties can be attributed to the graphene interlayer slows the side reaction, facilitates interfacial charge‐transfer process and stabilizes the cathode structure. These results demonstrate that modifying LiNi0.5 Co0.2 Mn0.3 O2 (NCM523) cathode surface with graphene interlayer is conducive to enhance the electrochemical performance of all‐solid‐state lithium batteries. Abstract : The interfacial reaction mechanism between LiNi0.5 Co0.2 Mn0.3 O2 cathode and poly(propylene carbonate) solid polymer electrolyte was investigated. A composite cathode structure was designed by introducing a graphene interlayer on the cathode surface to suppress the side interfacial reaction and enhance the electrochemical performance.